A Socio-political Analysis of Paul Hirst’s Theory of Associative Democracy as Representing the English Pluralist Theory of the State. - Mahir Abdulwahid Aziz (Zanco Journal of Humanity Sciences)
This theoretical study lies at the intersection of sociology, political science, and democratic theory. The study attempts to assess the validity of the resurgence of interest in the pluralist theories of the state, especially the contemporary English pluralist theory. In doing so, the study will be focusing on the critical account and assessing the main theoretical debates of the British sociologist and political scientist Paul Hirst (1946-2003). It should be emphasised that this study has been done according to a historical and explanatory approach method, which applied in both fields of political theory and Political Sociology. Therefore, the study offers a socio-political interpretation and exploration of Professor Paul Hirst’s main themes and debates on Associative Democracy in a descriptive way. The study consists of ten sections. Section one is devoted to the introduction. The second section is explaining the objectives of the study and the method in which used in the study. The third section explores the vital questions of the study. The fourth section deals with a short biography on Paul Hirst. Section five is exploring the idea of Associationalism. Section six is exploring Paul Hirst’s arguments on Pluralism, the English pluralist theory and the state. Section seven deals democracy, the welfare state and the "Third Way”, from Paul Hirst’s point of view. Section eight presents a critical assessment of representative democracy, by the exploration of Paul Hirst's associative democracy, governance and the free market economy. Section nine is dealing with the crisis of existing democracy. The last section is devoted to the conclusion of the study.